Soil moisture dynamics study in drip irrigated Broccoli (Brassica oleracea var. italic) - KUMARI, ARTI; PATEL, NEELAM; MISHRA, A.K. (Journal of Soil and Water Conservation, 2025)
A field experiment was conducted at the Precision Farming Development Centre (PFDC), Water Technology Centre (WTC), Indian Agricultural Research Institute (IARI), New Delhi, to study moisture dynamics in sandy loam soil under drip-irrigated broccoli. The experiment consisted of nine treatments with three replications, assessing three irrigation levels (60%, 80%, and 100% of crop evapotranspiration) and three irrigation frequencies (daily, once every two days, and once every three days). Hydrus-2D, a water and solute transport model, was used to simulate soil moisture distribution in the root zone without extensive calibration. Frequency Domain Reflectometry (FDR) measured soil moisture content before irrigation and at 4-, 24-, 48-, and 72-hour intervals post-irrigation. This analysis was conducted thrice during the growing season, corresponding to the end of the first, second, and third months after transplanting. Results indicated spatial and temporal variability in soil moisture distribution, with moisture levels increasing with depth and remaining elevated post-irrigation across all layers and distances from the emitter. Simulation experiments revealed higher moisture content in sandy loam soil’s top layer (0 to 15 cm depth) and minimal percolation from the drainage boundary, less than 1% of applied water. Correlation between observed and simulated soil moisture values using Hydrus-2D was strong, indicating the model’s efficacy in predicting soil water distribution. Aside from that, the frequency of drip irrigation had a significant (p: 0.05) impact on the yield of broccoli. With 80 per cent ETc and once-in-two-day irrigation, the highest yield (24.46 t/ha) was obtained followed by 100 per cent ETc with once-in-two-day irrigation. Overall, the study revealed that after irrigation, moisture content in the broccoli root zone exceeded field capacity and persisted for up to 24 hours. After 48 hours, moisture levels in the active root zone slightly decreased below field capacity. Consequently, irrigating broccoli in sandy loam soil every alternate day was recommended as the ideal cycle for achieving optimum broccoli yield.